The phantom menace - Dolan, Hannah (Dorling Kindersley readers. Beginning to read alone., 2012)
"Follow Jar Jar Binks through the Naboo swamp and see Darth Maul on his Sith speeder bike. Young readers will be on the edge of their seats as the LEGO toys and Star Wars come together in the fun retelling of the first prequel, Star Wars Episode I: The Phantom Menace."--Publisher.